Pemulihan Anak Korban Kekerasan Seksual Melalui Layanan Pendampingan oleh Unit Pelaksana Teknis Daerah Perlindungan Perempuan dan Anak Kabupaten Sidoarjo - Prima Rizky Aishah Muharomah (Jurnal Hukum Lex Generalis, 2025)
Sexual violence against children in Indonesia continues to increase, showing the weakness of the protection system and the lack of public awareness in reporting cases. Therefore, this study aims to analyze the impact experienced by child victims of sexual violence and the assistance services provided by the Regional Technical Implementation Unit for the Protection of Women and Children (UPTD PPA) of Sidoarjo Regency. The results showed that child victims experienced significant psychological, social, physical and educational impacts. Therefore, mentoring services by UPTD PPA, including legal assistance, health, social rehabilitation and social reintegration, play an important role in victim recovery. However, policy optimization and the role of the community are still needed to improve child protection.